(untitled) (Journal of Bio-Science, 2023)
Crotalaria L. is a genus of flowering plants in the family Fabaceae (subfamily Faboideae). Mitotic index is proportionately relevant to cell division rate; mitotic index was found higher (10.38±1.08%) in C. spectabilis and lower (9.43±0.304%) in C. juncea. The nuclear organizations were observed chromocentric in all examined species. The interphase chromosome volume was highest in C. juncea (0.596±0.27 µ³ in meristematic cell and 0.408±0.21 µ³ in differentiated cell) and lowest in C. saltiana (0.205±0.31 µ³ in meristematic cell and 0.16±0.25 µ³ in differentiated cell) which do not correlated with the somatic chromosome number but may be related with environmental condition. The largest cell size was found in C. juncea (20.47±0.49 µm2 in meristematic cell and 106.47±0.63 µm2 in differentiated cell) and the smallest in C. saltiana (14.43±0.39 µm2 in meristematic cell and 45.86±0.21 µm2 in differentiated cell). It was also observed that, the mean value of cell size was larger in differentiated cell compared to meristematic cell in all the studied species of Crotalaria. Chromocenter numbers were found highest (13.66±0.14) in C. saltiana and lowest (9.50±0.32) in C. juncea which are considered as more primitive and more advance in nature, respectively. Percentages of heterochromatin per nuclear area were found highest (14.75±0.71) in C. saltiana and lowest (9.67±0.71) in C. juncea which are considered as more primitive and more advance in nature, respectively. J. Bio-Sci. 30(2): 79-88, 2022